Discovery of a new class of potent pyrrolo[3,4-c]quinoline-1,3-diones based inhibitors of human dihydroorotate dehydrogenase: Synthesis, pharmacological and toxicological evaluation - Dimitrijević, Marina G.; Roschger, Cornelia; Lang, Kevin; Zierer, Andreas; Paunović, Milica G.; Obradović, Ana D.; Matić, Miloš M.; Pocrnić, Marijana; Galić, Nives; Ćirić, Andrija; Joksović, Milan D. (Bioorganic chemistry, 2024)
[Display omitted] •Pyrrolo[3,4-c]quinoline-1,3-diones were prepared by cyclization cascade reactions.•New class of potent hDHODH inhibitory demonstrated better activity than leflunomide.•Very low cytotoxicity against healthy HaCaT cells was observed.•The optimal lipophilicity was determined at physiological pH value.•The toxicological profile of the most active compounds was evaluated. Twenty N-substituted pyrrolo[3,4-c]quinoline-1,3-diones 3a-t were synthesized by a cyclization reaction of Pfitzinger's quinoline ester precursor with the selected aromatic, heteroaromatic and aliphatic amines. The structures of all derivatives were confirmed by IR, 1H NMR, 13C NMR and HRMS spectra, while their purity was determined using HPLC techniques. Almost all compounds were identified as a new class ofpotent inhibitors against hDHODH among which 3a and 3t were the most active ones with the same IC50 values of 0.11 μM, about seven times better than reference drug leflunomide. These two derivatives also exhibited very low cytotoxic effects toward healthy HaCaT cells and the optimal lipophilic properties with logP value of 1.12 and 2.07 respectively, obtained experimentally at physiological pH. We further evaluated the comparative differences in toxicological impact of the three most active compounds 3a, 3n and 3t and reference drug leflunomide. The rats were divided into five groups and were treated intraperitoneally, control group (group I) with a single dose of leflunomide (20 mg/kg) group II and the other three groups, III, IV and V were treated with 3a, 3n and 3t (20 mg/kg bw) separately. The investigation was performed in liver, kidney and blood by examining serum biochemical parameters and parameters of oxidative stress.